2006
DOI: 10.1103/physrevlett.97.107001
|View full text |Cite
|
Sign up to set email alerts
|

Increase inTcupon Reduction of Doping inLixZrNClSuperconductors

Abstract: We revealed a detailed phase diagram of the very lightly doped regime in Li-intercalated superconductors, LixZrNCl, to which previous studies have never gained access owing to the difficulty in synthesizing single-phase samples. A continuous and uniform Li intercalation without any indication of phase separation was carefully confirmed by means of synchrotron x-ray diffraction and Raman scattering experiments. Upon reducing the carrier density below x=0.12, we found a rapid increase in the superconducting tran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
130
2

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 117 publications
(138 citation statements)
references
References 25 publications
6
130
2
Order By: Relevance
“…In 2D, the density of states is a constant function of the Fermi energy ( F ) and, in principle, T c is expected to be insensitive on doping. Surprisingly, measurements on Li x ZrNCl [13,14,16], a weakly-doped multivalley 2D semiconductor, revealed that T c not only does not increase with doping but even decreases. Here we show that the e-e interaction is responsible for such a puzzling behavior.…”
mentioning
confidence: 99%
“…In 2D, the density of states is a constant function of the Fermi energy ( F ) and, in principle, T c is expected to be insensitive on doping. Surprisingly, measurements on Li x ZrNCl [13,14,16], a weakly-doped multivalley 2D semiconductor, revealed that T c not only does not increase with doping but even decreases. Here we show that the e-e interaction is responsible for such a puzzling behavior.…”
mentioning
confidence: 99%
“…the Kondo effect [1], the many-body localization transition [2], or the superfluid to Bose-glass (BG) [3,4] transition at finite disorder for lattice bosons [5][6][7]. While counterintuitive, in some situations disorder may enhance long-range order, as discussed for inhomogeneous superconductors [8][9][10]. Perhaps even more surprisingly, doping gapped antiferromagnets with a finite concentration of magnetic or non-magnetic impurities can fill up the bare spin gap with localized levels [11-13] which may eventually order, in the strict sense of macroscopic long-range order (LRO) at low temperature.…”
mentioning
confidence: 99%
“…In the superconducting state, the density of states recovers rapidly upon increasing the magnetic field [7], suggesting some kind of anisotropic pairing. As for the doping dependence, the DOS at the Fermi level stays nearly constant, but, for Li x ZrNCl, T c shows an increase upon lowering the carrier concentration until a sudden superconductor-insulator transition [13]. On the other hand, in Li x HfNCl, T c stays nearly constant in the doping range x < 0.5 [14].…”
Section: Introductionmentioning
confidence: 82%
“…It is hence interesting to investigate experimentally the possibility of time reversal symmetry breaking in the superconducting state of this material. The rapid recovery of the specific heat by applying the magnetic field [7], and also the unusual doping dependence of both the T c and the magnitude of the gap [13,14,18] remain as interesting future problems.…”
Section: Application To β-Mnclmentioning
confidence: 99%